R&D Activities for Fusion DEMO in the QST Rokkasho Fusion Institute. (17th November 2021) - Ishii, Y.; Aiba, N.; Ando, M.; Asakura, N.; Bierwage, A.; Cara, P.; Dzitko, H.; Edao, Y.; Gex, D.; Hasegawa, K.; Hayashi, T.; Hiwatari, R.; et al.
Abstract: The current status and the progress of research and development (R&D) activities for a Fusion DEMO reactor in the National Institutes for Quantum and Radiological Science and Technology (QST) Rokkasho Fusion Institute is reported. In order to advance the Japanese DEMO activity, not only Japanese domestic activity but also international collaborations of Broader Approach activity and ITER-related activities are conducted in the QST Rokkasho Fusion Institute. Activities for DEMO design and relevant R&D; design of a fusion neutron source and development of an accelerator, ITER Test Blanket System; tritium handling technology; and information technology infrastructures, including a supercomputer system and a remote experimentation system, are carried out for a Fusion DEMO reactor.